2015
DOI: 10.1103/physrevb.91.014307
|View full text |Cite
|
Sign up to set email alerts
|

Phonon anharmonicity in silicon from 100 to 1500 K

Abstract: Inelastic neutron scattering was performed on silicon powder to measure the phonon density of states (DOS) from 100 to 1500 K. The mean fractional energy shifts with temperature of the modes were ∆εi/εi∆T = −0.07 giving a mean isobaric Grüneisen parameter of +6.95±0.67, significantly different from the isothermal parameter of +0.98. These large effects are beyond the predictions from quasiharmonic models using density functional theory (DFT) or experimental data, demonstrating large effects from phonon anharmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 47 publications
5
52
0
Order By: Relevance
“…In another study describing felodipine-loaded PCL microspheres, PCL (80 kDa) had the most viscous organic phase, so the encapsulation efficiency was the highest. 37 In our study, this trend was more pronounced for high Mw PCL microspheres in which gelatine was also used.…”
Section: Loading and Encapsulation Efficiencymentioning
confidence: 46%
See 2 more Smart Citations
“…In another study describing felodipine-loaded PCL microspheres, PCL (80 kDa) had the most viscous organic phase, so the encapsulation efficiency was the highest. 37 In our study, this trend was more pronounced for high Mw PCL microspheres in which gelatine was also used.…”
Section: Loading and Encapsulation Efficiencymentioning
confidence: 46%
“…41 It was indicated that the viscosity of the organic phase of high Mw PCL was higher than that of low Mw PCL. 37 Microspheres prepared with PVA-gelatin were smoother and more homogeneous than those prepared with PVA (4%). Similar positive effects of gelatin use have been reported in other studies.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A comparison is interesting. Diamond cubic Si has a large pure anharmonicity at ambient pressure, several times larger than quasiharmonic effects from thermal expansion 13 . At ambient pressure, the average thermal shift of the phonon modes of Si 24 (red line in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…where γ is the thermal Gruneïsen parameter and v Si is the equilibrium atomic volume, which would yield a correction of 1.2 k B /atom (with the correction restricted to core atom) if one were to consider v rel = −20Å 3 and γ from [56]. The relaxation volume v rel defined in equations (3) and (4) may differ from the relaxation volume derived from the thermodynamical formation volume…”
Section: Vibrational Formation Entropymentioning
confidence: 99%